Toxicity, pharmacokinetics, and effectiveness of the ortho-chlorinated bispyridinium oxime, K870. (September 2022) - Zdarova Karasova, Jana; Kassa, Jiri; Hepnarova, Vendula; Pejchal, Jaroslav; Junova, Lucie; Andrys, Rudolf; Malinak, David; Bzonek, Petr; Kohoutova, Zuzana; Musilek, Kamil
Abstract: Oxime reactivators are causal antidotes for organophosphate intoxication. Herein, the toxicity, pharmacokinetics, and reactivation effectiveness of o -chlorinated bispyridinium oxime K870 are reported. Oxime K870 was found to have a safe profile at a dose of 30 mg/kg in rats. It exhibited rapid absorption and renal clearance similar to those of other charged oximes after intramuscular administration. Its isoxazole-pyridinium degradation product was identified in vivo . Although it showed some improvement in brain targeting, it was nevertheless rapidly effluxed from the central nervous system. Its reactivation effectiveness was evaluated in rats and mice intoxicated with sarin, tabun, VX, and paraoxon and compared with pralidoxime and asoxime. K870 was found to be less effective in reversing tabun poisoning compared to its parent unchlorinated oxime K203. However, K870 efficiently reactivated blood acetylcholinesterase for all tested organophosphates in rats. In addition, K870 significantly protected against intoxication by all tested organophosphates in mice. For these reasons, oxime K870 seems to have a broader reactivation spectrum against multiple organophosphates. It seems important to properly modulate the oximate forming properties (p K a ) to obtain more versatile oxime reactivators. Highlights: The chlorinated oxime K870 was found to have a safe profile at the dose of 30 mg/kg. K870 showed some improvement in brain targeting. K870 was able to reactivate blood AChE for all tested organophosphorus inhibitors (sarin, tabun, VX, and paraoxon). K870 significantly protected against sarin, tabun, VX, and paraoxon in mice.